Analisis Etos Kerja pada Kepemimpinan Kepala Pondok Pesantren Manbaul Ulum Muncar Banyuwangi - Ikhfiana Farika Putri; Camelia Qotrun Nada; Aniqotuzzuhro' Fitriana (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2023)
Islamic boarding schools as a place to hone religious knowledge in the view of Islamic law. Islamic boarding schools are places to study religion with kyai and ustadz and worship to seek knowledge by settling or living in the boarding school dormitories. In the Islamic boarding school environment, leadership plays an important role in the development and progress of Islamic boarding schools. Leaders must be able to advance the tasks and activities of an agency or organization. In developing Islamic boarding schools, the kyai have a right hand, namely the head of the Islamic boarding school, as a process of developing and organizing the daily activities of Islamic boarding schools so that they are more coordinated. This study uses qualitative data analysis techniques. The steps of data analysis include data reduction, data display, conclusion and verification. The results of this research analysis answer that the leadership of the Manbaul Ulum Islamic Boarding School currently has a leadership model that tends to be individual-collective in character. It is known that the implementation of leadership in Islamic boarding schools is still guided by the vision and mission of Islamic boarding schools. Meanwhile, in other aspects institutionally, Islamic boarding schools are under the auspices of foundations so that collective leadership collaboration is needed.